A New PETase from the Human Saliva Metagenome and Its Functional Modification via Genetic Code Expansion in Bacteria. Issue 12 (24th January 2023) - White, Mirren F. M.; Wallace, Stephen
Abstract: The discovery and engineering of new plastic degrading enzymes is an important challenge in chemical biotechnology to enable transition to a more sustainable and circular plastics economy. This field has so far yielded a range of enzymes and microbial pathways for the recycling and valorization of plastic waste. New research from Uttamapinant et al. reports the discovery of a novel polyethylene terephthalate (PET) hydrolase from the human saliva metagenome that displays improved properties and catalytic performance over previously characterized PET hydrolases (PETases). The authors also demonstrate the site‐specific incorporation of a photocaged unnatural amino acid, 2, 3‐diaminopropionic acid (DAP), which upon photodecaging enables covalent binding of DAP to the PET surface. Thus, this work highlights metagenomic datasets as an untapped source of new PET degrading enzymes and the chemical modification of PETases via genetic code expansion, enabling new biotechnologies for the circular plastics economy. Abstract : Uttamapinant et al. reported the discovery of new polyethylene terephthalate (PET) degrading enzymes from aquatic and human saliva metagenomes. Their catalytic performance is up to 83 times higher than known PETases. Site‐specific incorporation of an unnatural amino acid results in a stable acyl‐enzyme intermediate and a PET‐enzyme conjugate which can be imaged via confocal microscopy.